أحاديث غير الكتب الستة في كتاب "التذكرة" للإمام القرطبي دراسة تخريجية نقدية للخمسين حديثا الأولى من المائة الرابعة - بهيات، جنيد أحمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Imam Al-Qurtubi is an erudite polymath who is well known for his widely accepted commentary of the Holy Qur'an. The Imam's notable exegesis solidified him as a Qur'anic scholar, par excellence. However, the widespread study of his tafsir work has adversely cast a shadow on his intellectual achievements in various Islamic disciplines. From amongst these works is the book, “Al-Tadhkirah Bi Ahwaal Al-Mawta Wa Umur Al-Akhirah”. The Imam (may Allah be pleased with him) endeavoured to remind the reader of the inevitable reality of death, and the stages each soul will be made to go through thereafter. The value of the book is self-evident and timeless. However, the reputation of the book has invited unwanted attention from some critics who had used weak and even fabricated evidence against Imam Al-Qurtubi. Thus, this research is an attempt to unveil the ambiguity surrounding the authenticity of fifty Prophetic narrations (Ahadith) after three-hundred, as other students have already researched the first three-hundred narrations. The dissertation has been structured into three main chapters. The first chapter introduces the subject of research, and research methods applied throughout the study. The second chapter examines the life of Imam Al-Qurtubi with brevity, and the methodology he adopted in structuring the book. The third and final chapters scrutinized the fifty narrations, followed by the bibliography. The research methods deployed in this reseach are the survey method and the critical method. The first to compile the narrations from the book, and the latter to critically analiyze and grade the Hadith. After thorough investigation, the researcher concluded that seven traditions were Sahih li Dhatihi, two were Sahih li Ghayrihi, five were Hasan li Dhatihi, seven were Hasan li Ghayrihi, eleven were Da'if, six were Da'if Jiddan, nine were Mawdu', and three were left ungraded due to them not being found in the various books of Hadith used by the researcher.